Residual rocky forms in the landscape of the Outer Carpathians (Silesian Beskid Mts, Poland) – geotourist and sedimentological case study - Strzeboński, Piotr (Geotourism/Geoturystyka, 2023)
This study investigated residual landforms developed within of the flysch bedrock in the Outer Western Carpathians as sandstone-to-conglomeratic tors. The studied relic rocky forms are locally exposed on the valley slopes in the top and plateau parts of the Silesian Beskid Mts. The cognitive values of such relic landforms, especially in the context of their morphogenetic traits and shaping of their macro- and microrelief, are well known and described. In contrast to epigenetic processes, the sedimentological aspect of the origin of such siliciclastic rocky deposits is still subject to different approaches in terms of terminology and interpretation. Thus, the aim of this study is to describe the conditions of environmental settings and character of the sediment transport and deposition processes from gravity flows, and to present a depositional system model for such a variety of flysch deposits. This study also attempts to present geotourist and geoeducational attractiveness of the tors against the background of regional geodiversity, geoheritage, and geoprotection. The results yielded a synthetic morpho-litho-sedimentological and geotouristic specification of the rocky forms analysed. The residual rocky landforms are polygenic geomorphological elements developed as a consequence of multistage and different scale of morph-forming activity operating on the basis of litho-sedimentological and tectonic assumptions under the influence of denudation processes.